Image registration - Lim, Pei Yi (2016)
Image registration is widely used in today’s world as it is needed in remote sensing such as weather forecasting and environmental monitoring to allow work to be done efficiently. It is a process whereby two or more images overlay one another at different times of the similar scene. Practically, most image registration algorithms are measured in the separation between the images in order to get the transformation that these distances are at their lowest. Twodimensional and three-dimensional images are frequently used image registration in the medical applications. From the research, there are several of methods such as Scale Invariant Feature Transform (SIFT) and Speeded Up Robust Features (SURF) used in computer vision to form panorama image on different programs. Yet in this report, image stitching is being introduced using the C# program to implement where we are able to combine photographic images with overlapping scenes to achieve a segmented panorama image